Coingestion of carbohydrate and protein on muscle glycogen synthesis after exercise: A meta-analysis - Margolis, L. M.; Allen, J. T.; Hatch-McChesney, A.; Pasiakos, S. M. (Medicine & Science in Sports & Exercise, 2021)
Introduction/Purpose: 'Evidence suggests that carbohydrate and protein (CHO-PRO) ingestion after exercise enhances muscle glycogen repletion to a greater extent than carbohydrate (CHO) alone. However, there is no consensus at this point, and results across studies are mixed, which may be attributable to differences in energy content and carbohydrate intake relative to body mass consumed after exercise. The purpose of this study was determine the overall effects of CHO-PRO and the independent effects of energy and relative carbohydrate content of CHO-PRO supplementation on postexercise muscle glycogen synthesis compared with CHO alone. Methods: Meta-analysis was conducted on crossover studies assessing the influence of CHO-PRO compared with CHO alone on postexercise muscle glycogen synthesis. Studies were identified in a systematic review from PubMed and Cochrane Library databases. Data are presented as effect size (95% confidence interval [CI]) using Hedges` g. Subgroup analyses were conducted to evaluate effects of isocaloric and nonisocaloric energy content and dichotomized by median relative carbohydrate (high, =0.8 g/kg·h; low, <0.8 g/kg·h) content on glycogen synthesis. Results: Twenty studies were included in the analysis. CHO-PRO had no overall effect on glycogen synthesis (0.13, 95% CI = -0.04 to 0.29) compared with CHO. Subgroup analysis found that CHO-PRO had a positive effect (0.26, 95% CI = 0.04-0.49) on glycogen synthesis when the combined intervention provided more energy than CHO. Glycogen synthesis was not significant (-0.05, 95% CI = -0.23 to 0.13) in CHO-PRO compared with CON when matched for energy content. There was no statistical difference of CHO-PRO on glycogen synthesis in high (0.07, 95% CI = -0.11 to 0.22) or low (0.21, 95% CI = -0.08 to 0.50) carbohydrate content compared with CHO. Conclusion: Glycogen synthesis rates are enhanced when CHO-PRO are coingested after exercise compared with CHO only when the added energy of protein is consumed in addition to, not in place of, carbohydrate.